Evaluation: The International Journal of Theory, Research and Practice - Daniela C. Schröter (Journal of MultiDisciplinary Evaluation, 2005)
The first 2005 issue of Evaluation (Volume 11(1), January 2005) begins with two contributions to A Visit to the World of Practice, both of which focus on results-based evaluation and impact assessment within the context of the Millennium Development Goals (MDGs). Please visit http://ddp-ext.worldbank.org/ext/MDG/-home.do for information on the MDGs.